Efektivitas Implementasi Mediasi Sebagai Alternatif Penyelesaian Perkara Perceraian Di Pengadilan Agama Medan - Pramuningtias, Eko Indah; Hasanah, Uswatun (Kamaya: Jurnal Ilmu Agama, 2025)
The high divorce rate in the Medan region has led to various social impacts for those involved parties, making mediation an effective solution to reduce the increasing burden of divorce cases and as an effort to achieve peaceful and family dispute resolution. This research aims to examine the strategies of mediators and the implementation of mediation as an alternative for resolving divorce cases at the Medan Religious Court Class 1A during the 2021-2023 period. This study uses a qualitative method with an empirical juridical approach. Primary data was obtained through interviews with non-judge mediators at the Medan Religious Court, while secondary data was sourced from documents of the Medan Religious Court, relevant legislation, and literature. The results of the study indicate fluctuations in the success rate of mediation, which were 7.52%, 8.23%, and 4.96% respectively for the 2021-2023 period. Additionally, the implementation of mediation at the Medan Religious Court still faces various challenges. This research concludes that several enhancement measures are essential to achieve effective and efficient solutions in the mediation process at the Medan Religious Court. The recommended improvements encompass conducting public outreach and educational programs, upgrading facilities, implementing systematic evaluation and monitoring mechanism and engaging in comparative studies with Religious Court across other municipalities or regencies.